Can Hematological Parameters be a Indicator Risk Factor in the Development of Retinopathy of Prematurity? - Celik, Kiymet; Ekinci, Dilbade; Asena, Muhammet; Matur, Nilufer Okur (Klinische Pädiatrie, 2020)
Background Hematological parameters have been investigated as being indicative of increased inflammatory response in morbidity of very preterm infants. This study aims to determine whether the hematologic parameters and ratios of preterms can be an indicative risk factor for the development of retinopathy of prematurity (ROP).Materials-Methods This retrospective cohort study examined newborns born before 32 weeks. Twenty-three patients treated with the diagnosis of ROP were included in the patient group. The control group included 23 patients who did not have ROP (no-ROP). Medical records of eligible preterm infants were retrospectively reviewed. Hemogram samples obtained from all patients during the first 24 h of life and samples of their mothers obtained before delivery were evaluated. The hemogram parameters of white blood cell (WBC) count, neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, lymphocyte/monocyte ratio, and platelet mass index were calculated.Results No difference was observed between the groups in terms of demographic data. In terms of hematological parameters, maternal WBC counts of ROP patients were significantly higher than those of no-ROP patients and WBC counts of ROP patients were significantly lower than those of no-ROP patients.Conclusions This study found that high WBC counts in mothers before delivery and/or low WBC counts in preterms during the first postnatal day were higher in developed ROP. These results could lead to the development of prospective studies to assess the real prognostic value of WBC in ROP.
Keywords: White blood cell count; inflammation; retinopathy of prematurity; premature